If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(9x + -8) = 0 Reorder the terms: -1(-8 + 9x) = 0 (-8 * -1 + 9x * -1) = 0 (8 + -9x) = 0 Solving 8 + -9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -9x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -9x = 0 + -8 -9x = 0 + -8 Combine like terms: 0 + -8 = -8 -9x = -8 Divide each side by '-9'. x = 0.8888888889 Simplifying x = 0.8888888889
| -6x-5x=-11 | | -8=3x+4 | | 12x+6y=60 | | -15x^3+40x^2+35x=0 | | -35=n-17 | | -6=3(3+k) | | 6-(-10)= | | 5-4x-5=-8 | | -77=8x+3 | | -126=-18r | | -11=x-6 | | w^2-6w-8=0 | | 7a+8=57 | | 4(3-x)-8=5-(3x-2) | | 4u^2-25u+25=0 | | 53+(-18)= | | 52+-50= | | 5.4c+6=0.6(9c+10) | | 3t+7=13 | | 5x-6x-5=72 | | -3+14= | | 4d-6=2(3d-4) | | x^2-14x+196=0 | | -25+25= | | 78=-5x+19 | | 18=-5x+19 | | 33=-5x+19 | | 27=-5x+19 | | 2c+6=0.5(4c+12) | | 6a+5b-2a+-b+7a+3c+a= | | 3(x)+5=8 | | 13=(y+2)-3 |